Revisiting divisions of labour : the impacts and legacies of a modern sociological classic - Crow, Graham; Ellis, Jaimie (Manchester University Press, 2017)
This collection revisits Ray Pahl's 1984 sociology classic, combining excerpts from the original with assessments by leading researchers of how and why the book has stood the test of time as a study that fundamentally re-thinks our understanding of 'work'.